2011
DOI: 10.1177/1040638711403435
|View full text |Cite
|
Sign up to set email alerts
|

Baccharis megapotamica var. weirii poisoning in water buffalo (Bubalus bubalis)

Abstract: Abstract. An outbreak of an acute disease in buffalo (Bubalus bubalis) caused by the ingestion of Baccharis megapotamica var. weirii occurred in the southern region of Brazil. Ten out of 50 buffalo died 24-48 hr after being introduced into a pasture containing abundant amounts of the plant. Factors influencing the ingestion of the plant and consequent toxicosis included hunger, stress caused by shipment, and unfamiliarity with the plant. Clinical signs included serous ocular discharge, incoordination, mild blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
1
3
0
1
Order By: Relevance
“…In this region, a large amount of Baccharis megapotamica (Anjos 2018, personal communication) has also been observed, with clinical signs and lesions similar to those seen with B. coridifolia poisoning (Oliveira-Filho et al 2011, Panziera et al 2015. However, on the properties where the outbreaks occurred in this study, this plant was not found.…”
Section: Discussionsupporting
confidence: 49%
“…In this region, a large amount of Baccharis megapotamica (Anjos 2018, personal communication) has also been observed, with clinical signs and lesions similar to those seen with B. coridifolia poisoning (Oliveira-Filho et al 2011, Panziera et al 2015. However, on the properties where the outbreaks occurred in this study, this plant was not found.…”
Section: Discussionsupporting
confidence: 49%
“…Sob condições naturais há relatos de intoxicações pela var. weirii em bovinos (Tokarnia et al 1992, Driemeier et al 2000, ovinos (Pedroso et al 2010) e bubalinos (Oliveira-Filho et al 2011), e em condições experimentais há casos de intoxicação com ambas as variedades em bovinos, ovinos, coelhos (Tokarnia et al 2012) e bubalinos (Oliveira-Filho et al 2012). Na espécie caprina são descritos na literatura apenas casos de intoxicação experimental pela variedade weirii, no qual se verificou que a dose letal era a partir de 2g/Kg da planta fresca (Barbosa et al 1994).…”
unclassified
“…weirii was reported in water buffaloes of Brazil. The hepatic injuries that arisen from this toxicity were severe hepatocellular vacuolization with eosinophilic globules (councilman bodies) and clear lymphatic dilation in the portal areas (28). The hemorrhage abundance in the current study was 28.6% in confiscated livers (table 2).…”
Section: Discussionmentioning
confidence: 43%